Mild and Moderate Droughts in Savanna Ecological Zone Of Nigeria - Olatunde, Adewale Francis; Aremu, James K, (Advances in Social Sciences Research Journal, 2016)
Although drought studies have been carried out by many scholars in the Savanna Ecological zone of Nigeria over the years, few if any has been able to carry out the detailed year to year, decade to decade, and subperiod to subperiod analyses of the occurrences of mild and moderate droughts in this region over the years. This is because they are seen as not been destructive and therefore of not interest as the catastrophic extreme drought or the creepy invisible drought. This gap in study is what this study has tried to fill through the use of the Bhame and Mooley Drought Index (BMDI) as earlier used for extreme drought by Olatunde and Aremu, 2014. The results of the study show that there is no definite pattern of occurrence of mild and moderate droughts in the study zones during the study period. This emphasise the need for people of the zones to be always on the lookout for droughts of these magnitudes and others.